Respuesta :
Any arithmetic sequence can be expressed as:
a(n)=a+d(n-1), a(n)=nth term, a=initial term, d=common difference, n=term no.
Find the common difference.
-8--13=-3--8=2--3=d=5
The first term is -13 so a=-13, so our rule is:
a(n)=-13+5(n-1)
The above is what they might have, but it can be simplified further...
a(n)=-13+5n-5
a(n)=5n-18
a(n)=a+d(n-1), a(n)=nth term, a=initial term, d=common difference, n=term no.
Find the common difference.
-8--13=-3--8=2--3=d=5
The first term is -13 so a=-13, so our rule is:
a(n)=-13+5(n-1)
The above is what they might have, but it can be simplified further...
a(n)=-13+5n-5
a(n)=5n-18
arithmetic is an=a1+d(n-1)
a1=first term
an=nth term
d=common difference
n=which term
so
first term is -13
the next term is -8 which is 5 more than -13 so each term is 5 more than the previous, the common difference is 5
so
an=-13+5(n-1)
that is one equation
another one is
an=5n-18 (same equation but expanded and simplified)
a1=first term
an=nth term
d=common difference
n=which term
so
first term is -13
the next term is -8 which is 5 more than -13 so each term is 5 more than the previous, the common difference is 5
so
an=-13+5(n-1)
that is one equation
another one is
an=5n-18 (same equation but expanded and simplified)